2009
DOI: 10.1080/10640260902848592
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Implicit and Explicit Measures of Ego Functions and Distress Among Two Eating Disorder Subgroups: Outcomes of Integrative Treatment

Abstract: The study examined changes in ego functions and mental distress among eating disorder (ED) adolescent inpatients following integrative treatment. Participants included 31 restricting anorexia nervosa and 25 bingeing/purging spectrum ED inpatients. Rorschach Comprehensive System (CS; Exner, 2003) and self-report measures were administered on admission and discharge. We found that improvement in ego functions, mental distress and ED symptomatology occurred in both ED groups at discharge. Nevertheless, the two ED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…Accordingly, patients with AN-R are described more often as constricted and controlling their emotions than patients with AN-B/P and BN (Fassino et al, 2001; Vitousek & Manke, 1994), whereas patients with BN and AN-B/P are more likely to manifest deficient impulse and affect regulation (Vitosek & Manke, 1994). In a previous study of our group, significant between-group differences were revealed (Rothschild, Lacoua, & Stein, 2009), showing that inpatients with AN-R presented with higher levels of ego functions in comparison with patients with AN-B/P and BN, specifically on measures of impulse control and thinking disturbances.…”
Section: Personality Dynamics: Ego Functions In Ed Patientsmentioning
confidence: 59%
See 2 more Smart Citations
“…Accordingly, patients with AN-R are described more often as constricted and controlling their emotions than patients with AN-B/P and BN (Fassino et al, 2001; Vitousek & Manke, 1994), whereas patients with BN and AN-B/P are more likely to manifest deficient impulse and affect regulation (Vitosek & Manke, 1994). In a previous study of our group, significant between-group differences were revealed (Rothschild, Lacoua, & Stein, 2009), showing that inpatients with AN-R presented with higher levels of ego functions in comparison with patients with AN-B/P and BN, specifically on measures of impulse control and thinking disturbances.…”
Section: Personality Dynamics: Ego Functions In Ed Patientsmentioning
confidence: 59%
“…The study was conducted in an adolescent ED inpatient department located in a general hospital in central Israel. Data were derived from a longitudinal study described in previous studies (Rothschild et al, 2009; Rothschild, Lacoua, Eshel, & Stein, 2008), following female adolescent inpatients from the acute phase of their illness at admission to the phase of achieving stabilization in ED symptoms at discharge. The current participants were 62 female adolescent inpatients aged 13 to 18 years who (a) met Diagnostic and Statistical Manual of Mental Disorders , 4th edition (American Psychiatric Association, 1994) criteria for full-blown AN or BN at admission; (b) were never diagnosed with a bipolar disorder, schizophrenic spectrum disorder, substance use, organic brain disorder, or any medical disorder potentially affecting food consumption and weight (e.g., diabetes mellitus or thyroid disorders); and (c) continued with inpatient treatment until achieving and maintaining their required weight (for all patients with AN) and demonstrating no restricting, binging, and purging behaviors (for all patients) for at least a 2-week period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ao se tentar circunscrever esta ampla gama de investigações internacionais sobre o Método de Rorschach, acrescentou-se a palavra-chave "Adolescente" ao levantamento bibliográfico previamente realizado, por se tratar do foco do presente trabalho. Nesta nova pesquisa, o número de estudos encontrados se restringiu a 43, sendo 13 deles realizados com adolescentes que apresentavam algum transtorno mental (Ilonen et al, 2010;Kernier, Canouï, Golse, 2010;Bram, 2010;Balotti et al, 2009;Franks et al, 2009;Rothschild, Lacoua & Stein, 2009;Klinteberg, Johansson & Gacono, 2008;Kochinski et al, 2008;Rothschild et al 2008;Kimhy et al, 2007;Blatt, Besser, Ford, 2007;Grava et al, 2006;McGrath et al, 2005) e os demais trabalhos versavam sobre temas diversos desta etapa do desenvolvimento. Uma vez que a complexidade deste período de desenvolvimento pode ser disparadora para múltiplos focos de investigação científica, o pequeno número de trabalhos identificados na literatura científica internacional, indexada nesta reconhecida base de dados, sugere reduzido investimento sobre o processo de adolescência a partir do Psicodiagnóstico de Rorschach, método este capaz de acessar variáveis relevantes do processo de formação da personalidade.…”
Section: Estudos Com O Psicodiagnóstico De Rorschachunclassified
“…Tibon and Rothschild (2009) studied dissociative mechanisms in two samples of patients with anorexia (restrictive and B/P vomiting/purging forms) and bulimia (purging and non-purging). The Rorschach Reality Fantasy Scale (RFS; Smith, 1990), which stems from a psychoanalytic approach (Tibon et al, 2006) was used in addition to Rorschach CS variables. The RFS is based on Ogden's model (1985) and it provides an invitation to enter a transitional space between fantasy and reality.…”
Section: Comprehensive System Studiesmentioning
confidence: 99%